PENGARUH GOOD CORPORATE GOVERNANCE, FREE CASH FLOW, MANAJEMEN INVENTORY DAN LEVERAGE TERHADAP MANAJEMEN LABA - Suwanti, Sri; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to analyze the influence of good corporate governance, free cash flow, inventory management and leverage to the earning management. The population is all manufacturing companies which are listed in Indonesia Stock Exchange in 2011-2015. The sample selection has been done by using purposive sampling method and 45 companies or 225 observations have been obtained. But 3 of 225 companies which have been selected as observation samples are included as data outlier. Therefore, the remaining is 222 observation samples which can be applied in this research. The analysis method has bee done by using multiple linear regressions analysis method, determination coefficient (R2) classic assumption test, model feasibility (good of fit test/ F test) and hypothesis (t-test). The result of the research shows that simultaneously good corporate governance, free cash flow, inventory management and leverage give significant influence to the earnings management. Partially, good corporate governance does not give any significant influence to the earnings management, free cash flow gives negative and significant influence to the earnings management, inventory turnover and quick ratio does not give any significant influence to the earning management,and leverage gives positive and significant influence to the earning management.Keywords: Good corporate governance, free cash flow, inventory management, leverage, and earnings management.